Fabrication and optimization of n-cu2o thin film using electrodeposition method for homojunction solar cell - Mohd Hanif, Asyikin Sasha (2018)
Cuprous oxide (Cu20) is a promising semiconductor that has been getting attention as the alternative material for solar cell application. It is abundant, low cost and non-toxic to the environment. A homojunction Cu20 is said to provide high conversion efficiency for solar cell. However, as Cu20 is a natural p-type semiconductor, it is a challenge to make an n-type Cu20. In this study, n-Cu20 was prepared by using electrochemical deposition. The structural, morphological, optical and electrical properties of the electrodeposited Cu20 were evaluated after optimizing the parameters for Cu20 fabrication. Structural characterization of the deposited thin film was also done via X-Ray Diffractions (XRD) to confirm the existence of Cu20 particles on fluorine-doped tin oxide (FTO) substrate and to determine the crystalline phases of Cu20 in the sample. The surface morphology of Cu20 thin films were characterized by Field Emission-Scanning Electron Microscopy (FE-SEM) in order to examine the changes in the surface morphology of the film as the parameter varied. Ultra violetvisible (UV-Vis) spectrophotometer was used to study the optical absorption ofCu20 and to determine the band gap of the deposited thin film with further calculation including the thickness values of the thin film measured by surface profiler. The resistivity and sheet resistance of Cu20 thin film were detennined via four-point probe measurement test. Lastly, the deposited Cu20 thin film was confirmed as n-type by using the photoelectrochemical cell (PEC) test. The parameters for electrodeposition of Cu20 such as the deposition potential, pH solution, solution temperature, and deposition time were optimized at -0.10 V vs. Ag/ AgCl, pH 6.5, 60 °C, and 60 minutes, respectively. The band gap obtained from UV-Vis spectrophotometer was 2.45 eV. The successful fabrication of n-Cu20 will open a new door of Cu20-based homojunction development for thin film solar cell application.